Method of Radio-Emitting Target Identification from Passive Spatial Diversity Radio-Electronic Stations on the Basis of Student's t-Test - A. V. Kvasnov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The method of radar plot identification from the passive spatial diversity radio electronic stations is described. As mathematical model it’s used Student's t-test to check statistical hypotheses about averages. It was conducted simulation of the algorithm that showed his efficiency, and also considered an example of its realization.